Systematic Review: Misconceptions and Remediation on Momentum and Impulse - Pebriani, Tri Ulfa; Mufit, Fatni; Hidayati, Hidayati; Sari, Silvi Yulia (PILLAR OF PHYSICS EDUCATION, 2024)
This study aims to: (1) analyze the concepts that become misconceptions on momentum and impulse, (2) analyze the diagnostic test instrument used to identify students' misconceptions on momentum and impulse, (3) analyze the model/method/strategy/the approach used to remediate students' misconceptions on momentum and impulse, (4) analyze teaching materials/media used to remediate students' misconceptions on momentum and impulse, (5) analyze the effect of models/strategies/methods/media on improving students' conceptual understanding on momentum and impulse. The method applied in this research is a systematic review. The criteria for this study were article analysis carried out in a structured manner using descriptive statistical data analysis techniques for all research objectives and effect size to obtain research objective number 5. The database locations used in this study were Google Scholar, Neliti, Sinta, Garuda, Scopus, and Directory of Open Access Journals. The articles analyzed were twenty-six articles from national and international journals published in the last ten years. Based on the analysis that has been done, five research results were obtained. From the results of the study, it was found that: (1) concepts that often misconceptions are momentum, (2) Multiple choice tests with CRI and multiple-choice tests are often used to identify misconceptions on momentum and impulse, (3) model ECIRR is influential and widely used in remediation, (4) teaching materials/media that can be used for remediation are computer simulations, refutation text, and Concept Attainment-oriented worksheets, (5) the ECIRR model has a high influence on reducing misconceptions with an effect size 5,24. Based on the results of this study, a multiple-choice test instrument with the Certainty of Response Index (CRI) diagnostic test is suitable and easy to use to identify student misconceptions, to remediate misconceptions a good learning model is used, namely the ECIRR learning model, and can remediate misconceptions using computer simulations, refutation Concept Attainment oriented texts and worksheets as learning media/teaching materials.